MENCIPTAKAN STRATEGI BERSAING DENGAN INOVASI PRODUK DAN PEMANFAATAN DIGITAL MARKETING DI ERA MODERNISASI (STUDI PADA UMKM BUNGKUS IND) - Havisfal Alviansyah Alvian; Muhammad Fawaidul Muharrom; Agung Winarno; Agus Hermawan (Rafandha Press, 2023)
In the era of modernization, everyone is required to maximize the role of technology, until now the impact of this role has penetrated into digital marketing so that whatever consumers desire, the process of buying a product will be easier. So far the marketing carried out by Bungkus Ind products has not touched digital marketing at all so that access from consumers is also still not wide enough because the marketing process is not extensive only through grocery stores. This finally becomes a special concern when juxtaposed in the modern era like today. In the mentoring process for Bungkus Ind products, several activities have been carried out to spur these products to be able to take full advantage of digital marketing and Bungkus Ind products to be known as developing and advanced MSMEs. These activities include: (1) Introduction to packaging and branding, (2) making logos on packaging (3) printing new packaging (4) Product photos, (5) Introduction to social media and creating social media accounts, (6) Introduction to marketplaces and product registration on marketplaces such as Shopee. Of the many activities that have been carried out, the following results have resulted: 1. UMKM Wrap Ind now has a product logo as a feature of the product; 2. UMKM Wrap Ind now has attractive and contemporary packaging; 3. UMKM Wrap Ind which previously did not have accounts on social media and accounts at Shopee now have; 4. Business owners are beginning to have the enthusiasm to re-develop their business, are starting to actively participate in events and are more confident because their products already have packaging and logos that are easily recognized by the public. 5. Business owners gain knowledge on how to use digital media to increase sales. 6. Business owners have knowledge of how to create competitive strategies in the current market era which is very broad.